Synthesis and biological evaluation of quinones derived from natural product komaroviquinone as anti-Trypanosoma cruzi agents. Issue 15 (1st August 2015) - Suto, Yutaka; Nakajima-Shimada, Junko; Yamagiwa, Noriyuki; Onizuka, Yoko; Iwasaki, Genji
Graphical abstract